Effect of Anticoagulant Therapy on the Outcome of Descemet Membrane Endothelial Keratoplasty. Issue 9 (September 2021) - Loreck, Niklas; Geries, Carla; Schrittenlocher, Silvia; Siebelmann, Sebastian; Matthaei, Mario; Bachmann, Björn; Hayashi, Takahiko; Cursiefen, Claus
Abstract : Purpose: To analyze the effect of anticoagulant therapy (ACT) for systemic diseases on the outcome of Descemet membrane endothelial keratoplasty (DMEK). Methods: Consecutive eyes with Fuchs endothelial dystrophy that underwent DMEK between August 4, 2011, and July 15, 2016, were retrospectively analyzed. Data were obtained from the Cologne DMEK database at the University of Cologne, Germany. Best spectacle-corrected visual acuity (logMAR), endothelial cell density (at baseline and postoperatively up to 12 months), and rebubbling rates were compared between patients receiving ACT (ACT group) and those with no anticoagulant treatment (NCT group). Results: In this study, 329 eyes of 329 patients were included (ACT group n = 97, NCT group n = 232; mean age 69.9 ± 9.1 years). Bleeding was more common in the ACT group ( P < 0.001). Preoperative best spectacle-corrected visual acuity was 0.59 ± 0.44 and 0.48 ± 0.35 logMAR for the ACT and NCT groups, respectively, which improved to 0.13 ± 0.08 and 0.08 ± 0.16 logMAR, respectively, at 12 months postoperatively. No significant difference in endothelial cell density loss at 12 months was found between the groups (ACT group 36.2% ± 14.7%, NCT group 38.5% ± 15.1%; P = 0.467). Rebubbling rate was 19.6% in the ACT group and 28.9% in the NCT group ( P = 0.08). Conclusions: Although ACT increases the risk for preoperative and intraoperative bleeding in DMEK, there seems to be no negative effect on DMEK outcome. Thus, it is not advisable to stop ACT for DMEK surgery. Abstract : Supplemental Digital Content is Available in the Text.